The therapeutic potential and application of marine alkaloids in treating breast cancer - Yu, Jing; Wang, Xinmin; Du, Peixin; Shi, Hubing (Frontiers in Marine Science, 2024)
Breast cancer is a major threat to women’s health worldwide. Although the 5-year survival rate is relatively high, treating recurrent and metastatic breast cancer remains challenging. Existing anticancer drugs are often accompanied by adverse reactions; thus, there is an urgent need to explore safer and more effective treatment options. Marine natural compounds, especially alkaloids, are considered to be a potential treasure trove of new anticancer drugs due to their unique chemical structure and wide range of biological activities. A variety of marine alkaloids against breast cancer, including ecteinascidins, halichondrins, manzamines, and trabectedins, have opened new avenues for breast cancer treatment by employing multiple mechanisms, such as inducing cell apoptosis and autophagy, blocking cell cycle, inhibiting angiogenesis, targeting oncogene pathways, and inhibiting metastasis and invasion. Currently, Yondelis (trabectedin) has completed phase II clinical trials in patients with breast cancer and has shown certain efficacy. However, the clinical application of marine alkaloids still needs further research and development. This article deeply explores the mechanism of action of marine alkaloids against breast cancer and anticipates their clinical application prospects. With the deepening of research and the advancement of development, marine alkaloids are expected to bring new breakthroughs in breast cancer treatment.